2010
DOI: 10.1111/j.1365-2761.2010.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of opercular anomalies in gilthead sea bream, Sparus aurata L.: morphological and morphometric analysis

Abstract: Opercular anomalies are very frequent in reared gilthead sea bream and these can negatively influence the product value. Field observations have suggested that opercular malformations can recover over time. In order to verify this hypothesis, 140-day-old gilthead sea bream with monolateral opercular anomalies were divided into three groups, according to the type and increasing seriousness of the opercular malformations, and another group was composed of fish with bilateral opercular anomalies. All groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 22 publications
3
35
0
3
Order By: Relevance
“…). Nevertheless, exposure of gills due to lack or damage of opercular plate may affect respiration and marketability of the product (Beraldo & Canavese ). In the present study, the prevalence was high in comparison to previous studies (as reported below) and the cause(s) was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…). Nevertheless, exposure of gills due to lack or damage of opercular plate may affect respiration and marketability of the product (Beraldo & Canavese ). In the present study, the prevalence was high in comparison to previous studies (as reported below) and the cause(s) was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, anomalies of the gill cover have been recorded to affect mainly gilthead seabream (up to 80%: Koumoundouros ; a maximum of 9%: Cataudella et al . ; 5–20%: Beraldo & Canavese ), but also European seabass and a variety of candidate species, in some lots (Paperna ; Barahona‐Fernandes ; Francescon et al . ; Verhaegen et al .…”
Section: Skull Anomaliesmentioning
confidence: 99%
“…). The anomaly may expose fish to diseases and impact biological functions, and as a consequence performance, and product saleability (Beraldo & Canavese ; Boglione et al . ; Bruno, Noguera & Poppe ).…”
Section: Introductionmentioning
confidence: 99%